2009
DOI: 10.1002/jssc.200800679
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of novel phenylboronate affinity materials based on organic polymer particles for selective trapping of glycoproteins

Abstract: We report on synthesis concepts for the fabrication of various novel phenylboronate affinity materials based on polymethacrylate epoxy beads (Fractogel EMD Epoxy (M) 40-90 microm) and the testing of these functionalized polymer particles for selective trapping of a glycoprotein from a standard mixture containing a glycosylated and a nonglycosylated protein. Two inherently different approaches for the functionalization of the bare beads with boronate groups have been elucidated. In the first, the epoxy residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 48 publications
(27 reference statements)
0
24
0
1
Order By: Relevance
“…Since boronic acids form a covalent and reversible interaction with cis-diols in water [15], it is a little surprising that boronic acids have been widely used as affinity ligands for the separation of carbohydrates [16], glycoproteins [17,18], and nucleotides [19]. Boronic acid-containing adsorbents with good adsorption selectivity toward cis-diols are usually prepared by a copolymerization procedure or a chemical modification procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Since boronic acids form a covalent and reversible interaction with cis-diols in water [15], it is a little surprising that boronic acids have been widely used as affinity ligands for the separation of carbohydrates [16], glycoproteins [17,18], and nucleotides [19]. Boronic acid-containing adsorbents with good adsorption selectivity toward cis-diols are usually prepared by a copolymerization procedure or a chemical modification procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism can be explained that the boronic acid can covalently bind with cis-diols to form five-or six-membered cyclic esters in a basic aqueous media; the reversible disassociation can be performed under acidic conditions. The excellent specificity makes boronate groups potential affinity ligands for specific recognition and isolation of cis-diol-containing compounds, including catechols, nucleotides, carbohydrates, nucleosides, glycopeptides, and glycoproteins [11][12][13][14]. In addition, the moderate acidic elution condition make boronate affinity well coupled with mass spectrometry for analysis of cis-diol biomolecules in -omics [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Similar functionalized materials were designed by Zheng et al reporting the surface initiated ATRP of 4-VBA in order to create P(4-VBA) chain grafted poly(glycidylmethacrylate- co -ethylenedimethacrylate) beads. It was shown that these materials were suitable for the enrichment of glycoproteins in complex biological samples including human serum samples to allow straightforward glycoproteome analysis [32,33]. Similar results were obtained using BA-functionalized nanodiamonds allowing the recovery of up to 75% of glycopeptides in biological samples [34].…”
Section: Responsiveness Of Boronic Acid Containing (Co)polymersmentioning
confidence: 78%